Frequency of Human Papillomavirus Infection, Coinfection, and Association with Different Risk Factors in Colombia (2011)
Purpose: The aims of this study were to provide new insights into infection patterns of six high-risk human papillomaviruses (HR-HPV-16, -18, -31, -33, -45, and -58) and two low-risk HPV types (LR-HPV-6 and -11), their association with risk factors and coinfection. Methods: Cervical samples of 2110 women were tested for the presence of HPV-DNA by polymerase chain reaction. Statistical analyses were performed to determine viral-type frequencies in single and multiple infections and association between infection and different risk factors. Results: HPV-16 was the most prevalent type among the studied population, followed by HPV-31. This last viral type showed a variable distribution between the different cities evaluated. The results showed distinct type-specific distributions among regions and a high association between absence of pregnancies, cities as Girardot and Leticia, the indigenous ethnicity, and coinfection. Conclusions: The results showed a variable distribution of HPV types according to the geographical region analyzed. In addition, data suggest that some sociodemographic-factors such as ethnicity, number of pregnancies, lifetime number of sexual partners, and geographic region were significantly associated, and our results showed little differences between single and multiple infections by HPV with regard to risk factors. Furthermore, these results provide relevant information that will allow assessing in further studies the impact that vaccination programs on these populations and the selective pressure would have on the distribution of HPV types. © 2011 Elsevier Inc.